HBsAg level defines different clinical phenotypes of HBeAg(−) chronic HBV infection related to HBV polymerase-specific CD8+ cell response quality - Peña-Asensio, Julia; Calvo-Sánchez, Henar; Miquel-Plaza, Joaquín; Sanz-de-Villalobos, Eduardo; González-Praetorius, Alejandro; Delgado-Fernandez, Alberto; Torralba, Miguel; Larrubia, Juan-Ramón (Frontiers in Immunology, 2024)
Background: HBe-antigen(Ag)-negative chronic hepatitis B virus (HBV) infection is characterized by little liver fibrosis progression and vigorous HBV-multispecific CD8 + T-cell response.To assess whether HBsAg level could discriminate different HBeAg-negative chronic HBV infection subtypes with dissimilar quality of HBV-specific CD8 + T-cell response.We recruited 63 HBeAg-negative chronic HBV infection patients in which indirect markers of liver inflammation/fibrosis, portal pressure, viral load (VL) and HBV-specific CD8 + cell effector function were correlated with HBsAg level.A positive linear trend between HBsAg level and APRI, liver stiffness (LS), liver transaminases, HBV VL, and a negative correlation with platelet count was observed. Frequency of cases with HBV-specific CD8 + T-cell proliferation against at least two HBV epitopes was higher in HBsAg<1000 IU/ml group. CD8 + T-cell expansion after HBVpolymerase456-63-specific stimulation was impaired in HBsAg>1000 IU/ml group, while response against HBVcore18-27 was preserved and response against envelope183-91 was nearly abolished, regardless of HBsAg level. Cases with preserved HBVpolymerase456-63 CD8 + cell response had lower LS/duration of infection and APRI/duration of infection rates. HBV-polymerase456-63-specific CD8 + T-cell proliferation intensity was negatively correlated with LS/years of infection ratio.HBsAg>1000 IU/ml HBeAg-negative chronic HBV infection group shows indirect data of higher degree of inflammation, liver stiffness and fibrosis progression speed which are related to an impaired HBV-polymerase-specific CD8 + T-cell response.